THE USE OF GADGETS AS A SOURCE OF INFORMATION LITERACY IN SOCIOLOGY LEARNING: PENGGUNAAN GADGET SEBAGAI SUMBER LITERASI INFORMASI DALAM PEMBELAJARAN SOSIOLOGI - Vevy Julianty; Sudrajat (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The development of information technology has significantly transformed education, including Sociology learning. Gadgets have become essential tools in the learning process, serving not only as communication devices but also as primary sources of information literacy. This study aims to analyze the role of gadgets as information literacy sources in Sociology learning and their impact on students’ critical thinking skills and learning motivation. The research employed a literature study with a descriptive qualitative approach. Data sources were collected from scientific journals, reference books, and academic articles related to digital literacy and Sociology education published between 2019 and 2025. Data were gathered through searches in academic databases such as Google Scholar, ScienceDirect, and ResearchGate. The data were analyzed using content analysis techniques by identifying major themes, including the role of gadgets, information literacy, digital learning impacts, and implementation challenges. The findings reveal that guided gadget use can enhance students’ information literacy, access to learning materials, and engagement in learning activities. However, uncontrolled usage may lead to distraction and dependency. In conclusion, the integration of gadgets into the curriculum supported by teacher training and digital ethics education is essential to promote critical, adaptive, and character-based Sociology learning.